Research on Production and Characterization of Alpha Cellulose Derived from Rice Straw (Oryza sativa L.) - Harrizul Rivai; Annisa Suri Hamdani; Ramdani Ramdani; Rika Sari Lalfari; Regina Andayani; Fithriani Armin; Akmal Djamaan (Technological Innovation in Pharmaceutical Research Vol. 3, 2021)
It has been demonstrated that alpha cellulose can be generated from rice straw.Maceration of rice straw with ethanol, delignification with 3.5 % sodium hydroxide, extraction of alpha cellulose with 17.5% sodium hydroxide, and bleaching with hydrogen peroxide % were used to make alpha cellulose. The physicochemical properties of alpha cellulose were evaluated and compared to previous research in this study. Cellulose, along with lignin, is an organic compound found in plant cell walls that helps to cement the structure of the plant. The physicochemical properties include morphology by Scanning Electron Microscopy (SEM), crystallinity by X-ray Diffraction (XRD) analyses, functional groups by Fourier Transform Infrared (FTIR) Spectroscopy, loss on drying, pH and organoleptic. The SEM picture shows the morphology of cellulose fibres; the sample was semi-crystalline with a crystallinity index of 78%; the functional groups present in the sample are the same as those found in alpha cellulose; loss on drying was 8% w/w; pH was 7; and the organoleptic properties were white powder, odourless, and tasteless. The alpha cellulose yield is 30.11%.